Enterococcus faecium 1.15 Isolated from Bakasam Showed Milk Clotting Activity - Putranto, Wendry Setiyadi; Suradi, Kusmajadi; Chairunnisa, Hartati; Mustopa, Apon Zaenal; Kusumaningrum, Harsi Dewantari; Suhartono, Maggy Thenawidjaja (Annales Bogorienses, 2017)
Rennin-like protease of many microorganisms behave similarly to chymosin and are potential alternatives of rennet. The lactic acid bacteria with milk clotting activity were isolated from Bakasam, an Indonesian traditional fermented meat. Screening assay was carried out using modified method of skim milk agar and milk clotting activity test, and the isolate was then identified using 16S rRNA. We found 4 isolates that showed MCA of 18-20 SU/mL. Identification using 16S rRNA indicated that the isolate ALG.1.15 was 99% identical with Enterococcus faecium. The isolate potentially produced renin-like protease to subtitute renin from veal.